Clinical utility of methicillin-resistant Staphylococcus aureus nasal polymerase chain reaction (PCR) assays beyond respiratory infections - Haley M. Noeldner; Zachary J. Bliek; Nephi E. Jones; Ryan D. Prusa; Melissa S. Wilkinson; Amanda M. Bushman; Rossana Rosa (Antimicrobial Stewardship & Healthcare Epidemiology, 2022)
We estimated the predictive value of methicillin-resistant Staphylococcus aureus (MRSA) nasal polymerase chain reaction (PCR) for blood, bone, and soft-tissue cultures. The specificities were 88.8%, 88.5%, and 92.7% for all cultures, blood cultures, and bone and soft-tissue cultures respectively, and the negative predictive values were 99.3%, 99.8%, and 92.7% respectively.